THE CURRENT DEVELOPMENTS OF AGRICULTURAL BIOTECHNOLOGIES MARKET - A. M. Shkolyarenko (Vestnik MGIMO-Universiteta)
Population growth in the context of limited land resources makes the global scientific society research new ways to increase the agricultural yields. Over the past 20 years, biotechnology and GM crops have become widely spread and now are cultivated in 28 countries. The total area of crops has tripled, and it suggests the further vertical and horizontal integration in short term. In 2015, the US Department of Agriculture authorized the commercial use of GM farm animals. The development of agricultural biotechnology market is constrained by opponents of GM crops in more than 160 countries, which include Russia and the European Union, where the production of GM crops is banned due to economic, ethical, ideological and biological reasons. Currently, the EU is seeking to reduce the imports of GM crops and products; Russia's GM imports and exports are prohibited, and the deadline of designing a consolidated position on agricultural biotechnology has been moved to 2017. The author seeks to analyze the volume of production and international trade of agricultural products based on biotechnologies and to describe the main trends in the global market, which could be integrated into the food value chain in Russia. In the context of the worsening economic indicators, the article proposes the possibility of extending the use of GM crops in Russia non-food sector.